2006
DOI: 10.1007/s10140-006-0476-x
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of cervicocephalic arteries: early diagnosis and follow-up with magnetic resonance imaging

Abstract: Evaluate Magnetic Resonance (MR) and Magnetic Resonance Angiography (MRA) sensibility in the diagnosis and follow-up of dissection of Internal Carotid and Vertebral Artery (ICA/VA). We revalued MR examination of 36 patients, 24 men, 12 women, aged 18-69 years. All patients underwent brain TC and MR (GE 1 Tesla); in 16 subjects 3D Time-of-Flight (TOF-3D) MRA was performed and in 20 subjects a Contrast-Enhanced MRA (CEMRA) of neck and head arteries. Thirty-one patients underwent a MRA follow-up. Dissection invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…MRI/MRA had 50% to 100% sensitivity and 29% to 100% specificity [33,3539]. In a more recent study of CCAD in adults, contrast-enhanced MRA was 89% sensitive for detection of CCAD, versus 50% for TOF MRA [40]. This finding mimics our clinical experience.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…MRI/MRA had 50% to 100% sensitivity and 29% to 100% specificity [33,3539]. In a more recent study of CCAD in adults, contrast-enhanced MRA was 89% sensitive for detection of CCAD, versus 50% for TOF MRA [40]. This finding mimics our clinical experience.…”
Section: Introductionsupporting
confidence: 69%
“…MRI/MRA can perform favorably compared with CA, and contrast-enhanced MRA is superior to TOF MRA. Compared with TOF MRA, contrast-enhanced MRA possesses several advantages in detecting arterial stenosis and dissection: imaging of the entire course of the cervical arteries in one acquisition [41], decreased overestimation of stenosis or occlusion due to slow flow [40], and fewer motion artifacts [42]. …”
Section: Introductionmentioning
confidence: 99%
“…A fat suppressed T1‐weighted series is useful in identifying a hyperintense thrombus in the vessel wall in the case of acute dissection. However, this hyperintense signal usually develops within a few days owing to the transformation of haemoglobin to methaemoglobin and is therefore not always visible in the hyperacute phase .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 79%
“…This case highlights the importance of MRI with MR angiography as a diagnostic method. Its resolution approaches the conventional angiography and is able to show intramural hematoma, especially when fat suppression techniques are used 8 . The complementary exam also showed that the dissection extended to the petrous portion of the carotid artery, which is an uncommon event because usually the temporal bone represents a barrier to the pathologic process 1 .…”
Section: Discussionmentioning
confidence: 99%